Challenges in the Diagnosis and Management of Patients with Fibrosing Interstitial Lung Disease - Leslie B. Tolle (Case Reports in Pulmonology)
Interstitial lung diseases (ILDs) are heterogeneous in their clinical presentation. Making a differential diagnosis of ILD requires a thorough medical history, clinical examination, serologies, high-resolution computed tomography (CT) scan, and, in some cases, bronchoalveolar lavage or surgical lung biopsy. Multidisciplinary discussion is recommended to improve diagnostic confidence. ILDs have a variable and unpredictable clinical course. Patients should be closely monitored to ensure that progression of ILD is detected promptly. This involves regular assessment of symptoms, lung function, and, where appropriate, high-resolution CT. Patients with some fibrosing ILDs may respond well to immunosuppressants, but even patients who respond well to immunosuppressants initially may later show deterioration despite appropriate management. The tyrosine kinase inhibitor nintedanib has been approved for the treatment of idiopathic pulmonary fibrosis, other chronic fibrosing ILDs with a progressive phenotype, and systemic sclerosis-associated ILD. The three case studies described in this article illustrate the challenges in the diagnosis and management of patients with fibrosing ILDs and the importance of taking a multidisciplinary and individualized approach to care, including regular monitoring and consideration of whether a patient’s drug regimen needs to be changed when there is evidence of disease progression.